Emergencies in critical care - Beed, Martin; Mahajan, Ravi P.; Sherman, Richard (Oxford University Press, 2007)
This book is a practical, accessible guide to emergency situations encountered in critical care. The format allows the reader to gain vital clinical information in an easy-to-follow format without spending much time scanning through superfluous detail. Topics are covered in 2 parts: compromised systems and specific conditions.